7. Franz Joseph Strauss, a Joachim of the Horn - Gîscă Petrea (Review of Artistic Education, 2022)
Franz Joseph Strauss was one of the brightest horns of the 19th century. He was born in Germany and worked all his life in Munich, being a first - horn player, composer, conductor and teacher. As a composer he wrote two concerts for horn and orchestra and several pieces for horn and piano, most of them, the author singing them in the first absolute audition. As a teacher, he participated in the creation of a German horn school, and his studies for natural horn are still valid today. Difficult and sometimes misunderstood by musicians of the time, Franz Strauss remains a landmark in the history of the horn and a legend in the art of horn performance.